175 Does Knowing Pre-Operative Penile Length Influence Patient Satisfaction Post Penile Prosthesis Surgery. (1st May 2022) - Palasi, S.; Howell, S.; Green, T.; Kannady, C.; Slaughter, K.; Wang, R.; Yang, B.
ABSTRACT: Introduction: Patients may undergo penile prosthesis surgery (PPS) as a treatment option for erectile dysfunction (ED). Those who undergo PPS commonly complain of penile shortening after implantation. Furthermore, previous research has shown a decrease in penile length following inflatable penile prosthesis surgery compared to intracavernosal injection at 12 months. Objective: Therefore, we conducted a prospective, multicenter cohort study to determine whether knowledge of pre-operative penile length measurement influences post-operative treatment satisfaction and satisfaction with penile length. Methods: The cohort included a total of 102 patients undergoing PPS from August 2017 to December 2019. Study group participants underwent pre-operative penile length measurement (n=49) while the control group (n=53) did not undergo pre-operative measurement. Intra-operative and 6-week post-operative penile length measurements were later obtained in both groups. Six months post-operatively, patients were asked to complete the validated 14 item Erectile Dysfunction Inventory of Treatment Satisfaction (EDITS) questionnaire to assess both overall treatment satisfaction and satisfaction with penile length. Chi-square analysis was performed to determine whether a difference in satisfaction existed between the two groups. Results: We observed high patient satisfaction scores in both groups when using the EDITS questionnaire. Mean scores for overall treatment satisfaction were 3.57 and 3.53 (on a scale from 0 to 4) in the study and control group respectively. Mean scores for satisfaction with penile length were 4.08 and 4.11 (on a scale from 1 to 5) in the study and control group. There was no difference in overall satisfaction of treatment between those who knew their pre-operative length and those who did not ( p=0.483 ). We also found no difference in satisfaction of post-operative penile size between both groups ( p=0.645 ). Moreover, 59% of the combined cohort believed their overall sexual satisfaction was affected by penile length, with no difference between both groups ( p=0.463 ). We observed no significant decrease in mean penile length from pre-surgical intraoperative measurement to 6-week post-operative measurement (0.42 cm and 0.21 cm in study and control group, respectively) with no statistical difference between groups ( p=0.251 ). Conclusions: The study suggests that knowledge of pre-operative penile length does not influence 6-month post-operative satisfaction in patients who have PPS. Therefore, performing pre-operative measurement in clinic solely for the purpose of informing the patient may be unnecessary. Current interventions aimed at conserving penile length may be effective at maintaining patients' satisfaction with their penile length. The effects of other factors such as partner satisfaction, sex therapy, time after PPS, and the use of malleable versus inflatable penile prosthetic should be investigated in future studies. Disclosure: Work supported by industry: no.